The Relationship between Institutional Structure and Economic Growth: A Comparative Analysis for Selected Countries - Acaravci, Ali; Erdogan, Sinan (International Journal of Economics and Financial Issues, 2017)
This study explores the long-run relationship between institutional structure and economic growth for selected countries for 1993-2012 period by using dynamic panel data analysis. The results can be summarized as follows: i) There exists a cross-sectional dependence for variables and models ii) All variables are stationary at their first difference except for institutional indicator of second group. iii) There exists a cointegration relationship between non-stationary variables. iv) Institutional structure has positive and statistically significant impact on economic growth in First group of countries. v) There is no significant relationship between institutional structure and economic growth in second group of countries. vi) Gross capital formation has positive impact on economic growth in both groups. Keywords: Institutional Economics, Institutional Structure, Economic Growth, Panel Data Analysis, International Country Risk Guide. JEL Classifications: C33, D72, O50